Saturday

April 19, 2014

April 19, 2014

Posted by **DANIELLE** on Thursday, December 21, 2006 at 10:14am.

2m=n-3

3m=2n-9

Just replace n with (2m + 3) in the second equation. Then solve for m. Once you know the value of m, use either of your equations, such as n = 2m+3, to get n.

**Related Questions**

Substitution Method-Plz help - Use the Substitution method to solve the system ...

subsitution method - Can some one show me how to use the Substitution method to ...

substitution method - solve by the substitution method 2m+n=9 m-6n=50 the ...

Substitution Method - Use the Substitution method to solve the system of ...

Math/116 week seven - solve by the substitution method. 2m+n=1 m-9n=10

math - Match the equation with the step needed to solve it. 1. 2m - 1 = 3m ...

math - Match the equation with the step needed to solve it. 1. 2m - 1 = 3m ...

Algebra 2345678!! - Solve the system of equations using the Addition method. 2a...

Linear Equations - Can you please help solve this equation using the ...

Math - How do I solve these problems, I really need help. Solve by substitution ...